KECERDASAN INTERPERSONAL, INTRAPERSONAL DAN KECERDASAN EMOSI SISWA KELAS V SD MUHAMMADIYAH PONOROGO - Pryla Rochmahwati; Mufidatul Afifah (IAIN Ponorogo, 2018)
Abstract: This study aims to determine the correlation between three variables, namely, interpersonal, intrapersonal and emotional intelligence at the fifth grade students in Muhammadiyah Elementary School Ponorogo at the 2016/2017 Academic Year. It employed correlational research design. The population of this present research was 125 students of the fifth grade students in Muhammadiyah Elementary School Ponorogo and it assigned 94 students as sample by using proportinate random sampling technique. The data was collected through questionnaire. It utilized multiple correlations formula by using SPSS 16 for Windows as data analysis. The findings showed that there is significant correlation of interpersonal and intrapersonal intelligence on emotional intelligence at the fifth grade students in Muhammadiyah Elementary School Ponorogo at the 2016/2017 Academic Year and its value was 0.75.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan tingkat korelasi kecerdasan interpersonal dan intrapersonal dengan kecerdasan emosi siswa kelas V SD Muhammadiyah Ponorogo tahun pelajaran 2016/2017. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kuantitatif berjenis korelasional. Populasi dalam penelitian ini adalah 125 siswa. Dengan menggunakan teknik proportinate random sampling diperoleh 94 siswa sebagai sampel. Adapun teknik analisis data yang digunakan yaitu menggunakan teknik korelasi berganda dengan menggunakan bantuan SPSS versi 16.0 for windows. Hasil analisis menunjukkan bahwa terdapat korelasi yang signifikan antara kecerdasan interpersonal dan intrapersonal dengan kecerdasan emosi siswa kelas V SD Muhammadiyah Ponorogo tahun pelajaran 2016/2017 dengan nilai korelasi sebesar 0,75.